Overexpression of EMT-related transcription factors SNAI1 and ZEB1 is associated with more aggressive clinicopathological features of pancreatic cancer - Kestutis Urbonas; Gabija Stachneviciute; Aldona Jasukaitiene; Povilas Ignatavicius; Zilvinas Dambrauskas; Antanas Gulbinas; Giedrius Barauskas (PLoS ONE, 2026)
Background/Objectives Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal malignancies due to its aggressive nature and resistance to therapy. The epithelial-mesenchymal transition (EMT) drives cancer progression, regulated by transcription factors (TFs) such as SNAI1, SNAI2, ZEB1, ZEB2, and TWIST. This study evaluates EMT-TF expression in PDAC and its clinical relevance. Methods PDAC tissues from 45 patients were analyzed using qRT-PCR and Western blot. Clinical features and survival outcomes were statistically examined for correlations with EMT-TF levels. Results mRNA levels of SNAI1 (16.4-fold, p = 0.02), SNAI2 (21.8-fold, p = 0.028), ZEB1 (17.2-fold, p = 0.037) were significantly elevated in PDAC tissues compared to healthy controls. TWIST showed 3.75-fold increase in PDAC tissue; however, this elevation was not significant (p = 0.124). Corresponding protein-level increases were observed for Snail1/Slug and Zeb1. High SNAI1 expression correlated with peripancreatic invasion (p = 0.026) while ZEB1 overexpression was significantly associated with shorter survival (15.2 vs. 33.3 months, p = 0.037) and remained an independent prognostic factor in multivariate analysis. ZEB2 mRNA was reduced, however, protein levels were elevated. TWIST mRNA overexpression was not reflected at the protein level. Conclusions Overexpression of EMT transcription factors SNAI1 and ZEB1 reflect more aggressive histopathological patterns of PDAC. The strong correlation of SNAI1 expression with the expression of other EMT-TFs highlights its’ role in peripancreatic invasion, as well as impact on overall survival and may serve as an argument defining the leading role of SNAI1 in this context.